2017
DOI: 10.1016/j.jdiacomp.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Early declines in physical function among aging adults with type 2 diabetes

Abstract: Aims Type 2 (T2DM) diabetes is associated with reduced physical function and early disability. We hypothesized that changes in physical function occur early and differ by age. Our aims were to determine and compare differences in and predictors of physical function in older and younger adults with T2DM. Methods Eighty adults completed six-minute walk distance (6MWD) tests, wore wrist actigraphy for 5 days and completed diabetes health and symptom surveys. Comparative and bivariate analyses were completed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Bi et al () reported that young age was associated with poor glycaemic control, while Cowie et al () observed a higher prevalence among the middle‐ and older‐aged adults. Furthermore, Bi et al () and Lee et al () found out that shorter duration of diabetes was related to tighter glycaemic control but Fritschi et al () observed a poor glycaemic control. In addition, with the inconsistent findings in the literature review regarding ethnicity (Lanting et al, ; Rothman et al, ) and BMI (Anari et al, ; Bae et al, ) affecting glycaemic control, further studies should be established to understand the relationship among the different variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bi et al () reported that young age was associated with poor glycaemic control, while Cowie et al () observed a higher prevalence among the middle‐ and older‐aged adults. Furthermore, Bi et al () and Lee et al () found out that shorter duration of diabetes was related to tighter glycaemic control but Fritschi et al () observed a poor glycaemic control. In addition, with the inconsistent findings in the literature review regarding ethnicity (Lanting et al, ; Rothman et al, ) and BMI (Anari et al, ; Bae et al, ) affecting glycaemic control, further studies should be established to understand the relationship among the different variables.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting relationships regarding age (Bi et al, 2010;Cowie et al, 2010) and duration of disease (Bi et al, 2010;Fritschi et al, 2017;Lee et al, 2016) in relation to glycaemic control. Bi et al (2010) reported that young age was associated with poor glycaemic control, while Cowie et al (2010) observed a higher prevalence among the middle-and older-aged adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T he prevalence of type 2 diabetes is increasing worldwide 1) . According to a previous study, diabetic patients may present with motor skills deficits 2) ; additionally, an early decline in physical function with age has been associated with type 2 diabetes 3) . These facts represent a serious problem, as the number of people aged >65 years is expected to continue to rise in developed countries such as Japan, Germany, and Italy 4) .…”
mentioning
confidence: 96%
“…Type 2 diabetes mellitus (T2DM) is one of multiple age-related metabolic diseases [ 1 ]. Several latest studies have demonstrated severe and progressive abnormalities in brain structures and cognition during the early stage of T2DM [ 2 ].…”
Section: Introductionmentioning
confidence: 99%